(untitled) (REGE Revista de Gestão, 2023)
Purpose: This study aims to analyze the relationship between telework and teleworkers’ characteristics and the work-nonwork conflict (WNWC) in the Brazilian context, investigating time spent in eight nonwork dimensions and the more affected dimensions. Design/methodology/approach: The study was quantitative and descriptive. A survey was conducted with 299 professionals teleworking in Brazil. Data analysis was conducted through descriptive statistics, Pearson’s correlation, and analysis of variance. Findings: Results show diversified interests other than work and family among teleworkers, variation within the affected nonwork dimensions in the WNWC, and that teleworkers’ WNWC is negatively associated with time flexibility and manager support and positively associated with individual preference for segmentation as a boundary management strategy. Research limitations/implications: The study highlights the need to include more nonwork aspects in telework studies to influence organizational practices. The main limitation is the non-probabilistic sample. Practical implications: Knowing more about teleworkers’ WNWC will help organizations improve lives by implementing practices and building a cultural environment that preserves nonwork time. Social implications: The study reinforces demands from new family arrangements and an aging society: organizations have to prepare to have teleworkers who want or need to dedicate time to interests besides family or children. Originality/value: It progresses towards a broad understanding of nonwork besides family to understand teleworkers’ WNWC.